Mulheres e crimes: um diálogo com os direitos humanos das detentas em Manaus - Lima, Neuton Alves De (2017)
This research seeks to understand in this research the multifaceted universe of women involved in crimes that encounter private freedom in the Center for the Provisional Detention of Women in Manaus and in the Anísio Jobim Penitentiary Complex. With support for women's doctrine and feminist criminology, the motives that move these women to the world of crime are discussed. Based on the prison studies approach, it makes an inroads into the main causes of violence and points out which groups of people become the preferred targets of the policy of mass incarceration adopted as a means of containing violence. We also identify the main characteristics of the sociodemographic and economic profile of detainees, through graphs and maps elaborated from the official data of the prison administration. It is also questioned whether the human rights of women detained in Manaus are being fulfilled in the two prisons, based on visits, interviews, reports, observations and other documents related to the records of the life in the prison of these women.